analisis penggunaan aplikasi mobil banking Syariah untuk meningkatkan akses nasabah - Dea Riyanti Paramitha; Muhammad Iqbal Fasa (Jurnal Intelek Dan Cendikiawan Nusantara, 2024)
This research aims to analyze the use of Sharia mobile banking applications as ameans to enhance customer access to banking services. Sharia mobile bankingoffersbankingsolutionsthatcomplywithShariaprincipleswhilefacilitatingcustomers inconducting financial transactions more efficiently and practically.By analyzing customer behavior and the factors influencing the adoption of thistechnology, this research seeks to understand the extent to which Sharia mobilebanking applications can expand access to banking services, particularly amongcommunities underserved by conventional banking systems. This study employs alibraryresearch-basedanalysismethod.TheresultsareexpectedtoprovideinsightsintooptimalstrategiestoincreasetheutilizationofShariamobilebankingtechnology inordertoachieve broaderfinancialinclusion. keywords: syariahmobilebanking, customeraccess, bankingservices, technology, financialinclusion